Characterisation of nanoscale carbide precipitation in as-cast Co–Cr–W-based dental alloys. Issue 10 (10th February 2016) - Yamanaka, Kenta; Mori, Manami; Sato, Kazuhisa; Chiba, Akihiko
Abstract : The results of the present study indicate the importance of local chemistry along with carbide precipitation in the optimization of alloy design for achieving desirable properties such as high strength, ductility, and corrosion resistance in dental Co–Cr-based cast alloys. Abstract : Carbide precipitation in biomedical Co–Cr alloys significantly influences the performance in terms of mechanical properties and corrosion resistance. In this study, we examined the carbide precipitation associated with local solute partitioning in as-cast Co–Cr–W-based dental alloys at the micro- and nano-scale. Co–28Cr–9W–1Si (mass%) alloys with carbon concentrations ranging from 0.01 to 0.33 mass% were prepared. It was found that Cr, W, Si, and C segregated at the interdendritic regions of the face-centered cubic (fcc) γ-grain microstructures, resulting in precipitation; the amount of interdendritic precipitates was found to increase with increasing bulk carbon concentration. We identified, for the first time, the nanosized mixed-phase constituents, which were composed of ∼100 nm fine grains of the γ-phase and M23 C6 -type carbide, at the interdendritic regions of the high-carbon Co–Cr–W alloy. These nanosized M23 C6 carbides were produced with a cube-on-cube orientation relationship ([001]γ ||[001]M23 C6 and (100)γ ||(100)M23 C6 ) with the surrounding submicron γ-grains, while the local morphology changed from equiaxed to plate-like morphology. Nanoscale partitioning of the alloying elements was considered to be the origin of the interdendritic nanostructured constituents. As such, the nanoscale elemental partitioning was observed to alter the local mechanical properties and to affect the corrosion resistance of the alloys. The observed results indicate the importance of local chemistry—which has not received sufficient attention to date—along with carbide precipitation in the optimization of alloy design for achieving desirable properties such as high strength, ductility, and corrosion resistance in dental Co–Cr-based cast alloys.